2013
DOI: 10.1021/np400145u
|View full text |Cite
|
Sign up to set email alerts
|

Hytramycins V and I, Anti-Mycobacterium tuberculosis Hexapeptides from a Streptomyces hygroscopicus Strain

Abstract: Thirty-five thousand actinomycete extracts were screened for anti-Mycobacterium tuberculosis (M. tb) activity, followed by C18 cartridge fractionation of 37 prioritized extracts. Based on MICs against replicating and nonreplicating M. tb, and IC50 values against Vero cells to generate selectivity indices, seven fractions from seven different strains were selected for further examination. When cultured in G.S.S. media and extracted with ethyl acetate, the Streptomyces hygroscopicus strain ECUM 14046 yielded an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 34 publications
(52 reference statements)
0
12
0
Order By: Relevance
“…CNX037, isolated from sediment. Cai et al [ 37 ] have isolated two anti- Mycobacterium tuberculosis cyclohexapeptides from a Streptomyces hygroscopicus Strain, while Song et al [ 38 ] reported isolation of three new cyclopeptides, desotamides B–D, from the deep South China Sea-derived Streptomyces scopuliridis SCSIO ZJ46. To the best of our knowledge, compound 2 is the first cyclopeptide containing d -pipecolic acid residue ever isolated from marine fungi.…”
Section: Resultsmentioning
confidence: 99%
“…CNX037, isolated from sediment. Cai et al [ 37 ] have isolated two anti- Mycobacterium tuberculosis cyclohexapeptides from a Streptomyces hygroscopicus Strain, while Song et al [ 38 ] reported isolation of three new cyclopeptides, desotamides B–D, from the deep South China Sea-derived Streptomyces scopuliridis SCSIO ZJ46. To the best of our knowledge, compound 2 is the first cyclopeptide containing d -pipecolic acid residue ever isolated from marine fungi.…”
Section: Resultsmentioning
confidence: 99%
“…Several small and ultra-small cyclic peptides were reported to exert antimycobacterial activities, including griselmycins [28], depsidomycin [29], hytramycin [30], brunsvicamides [31], pyridomycin [32], hirsutellide A [33] and the wollamides [34]. …”
Section: Introductionmentioning
confidence: 99%
“…13 The ethyl acetate extract of ECUM14046 and the daughter fraction F3 were spotted on the NP-TLC plate, developed with EtOAc/Tol/MeOH/FA (95%) (60:40:5:1, v/v/v/v), and subjected to contact bioautography (Figure 4B). The zones of interest corresponding to the zones of inhibition on the agar plate were localized on the duplicate TLC plate ( R f 0.44 and 0.53).…”
Section: Resultsmentioning
confidence: 99%